2010
DOI: 10.12968/hmed.2010.71.5.47908
|View full text |Cite
|
Sign up to set email alerts
|

The World Health Organization Surgical Safety Checklist

Abstract: The World Health Organization produced the Surgical Safety Checklist to improve patient safety. This review examines the supporting evidence, the results of a study of its worldwide trial and discusses the possible mechanisms of its effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 14 publications
0
26
0
1
Order By: Relevance
“…Facility-external measurements can be performed for instance by government offices, the medical service of health insurers (MDK), patients, network auditors, and subsequent facilities along the patient pathway. Checklists such as those commonly used in QM audits are recommended for all three measurements [15], [16], [17]. …”
Section: Resultsmentioning
confidence: 99%
“…Facility-external measurements can be performed for instance by government offices, the medical service of health insurers (MDK), patients, network auditors, and subsequent facilities along the patient pathway. Checklists such as those commonly used in QM audits are recommended for all three measurements [15], [16], [17]. …”
Section: Resultsmentioning
confidence: 99%
“…70,406,551,552 Empirical research supports assertions that the WHOSSC (i) saves lives; [553][554][555][556][557] (ii) improves communication across the surgical team; 558 (iii) reduces the occurrence of wrong-site surgery; 63 (iv) promotes adherence to defined antibiotic protocols, thereby reducing the incidence of surgical-site infection; [559][560][561] and (v) fosters more efficient use of theatre time and resources, 556 while supporting appropriate staffing levels. 439 Despite such obvious benefits, operationalisation of the WHOSSC may be poor.…”
Section: Reducing Surgical Complicationsmentioning
confidence: 98%
“…Full compliance to checklists is often difficult to achieve and largely depends on many contextual factors. Compliance differs between hospitals and staff members and between specific sections and individual items of the checklist 57,1519. Variation in compliance has been noted: Borchard et al7 summarized 15 studies evaluating checklist compliance and found that overall compliance rates ranged from 12% to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Other prospective studies based on administrative data have indicated that, while items were documented as being checked, clinical behaviors underlying those checks were not observed 18,2022. While researchers have evaluated outcomes relative to checklist compliance,57,1519 there are currently no studies in this field that have evaluated strategies that support its implementation. As the main intent of using SSCs is to improve interdisciplinary communication among members of the surgical team, the implementation process should be aligned with this objective.…”
Section: Introductionmentioning
confidence: 99%